Madura Cattle Development and Local Cultural Innovation - Sumartono; Syaifuddin Zuhri; Suparno; Desy Kurniati Agustina; Rudy Haryanto (Future Science)
Madura cattle development is stagnant due to natural conditions, human resources and technology. The introduction of crossbreeding and insemination gains community resistance. There is an assumption that innovation will destroy local germ plasma. What should be done so that technical and social considerations can run synergic. This research to know the cattle in the cattle version and the interests of the community. The study was conducted by indepth interview to farmers group and agricultural extension Observations concerning what is desired and done breeders. The research is intended to know the pattern of cattle breeding conducted by farmers and government policy for livestock development. The results at the farmer level there are two patterns of cattle farming conventional ranchers and semi-intensive breeders. Conventional breeders want to keep local cattle. Cross cattle are rare. Origin of seeds and seed quality are not considered. Products are traded in the local market for cut (meat). Semi-intensive breeders, do breeding and exclude seed cattle. Products are traded at home. Selling price is three times higher than ordinary cattle. If there are cows that are less qualified, newly sold in the market. Breeding and selection of seeds into a new culture. The local government established Waru as a local Madura cattle breeding center. Other types of cattle are not allowed to enter. Thus Madura cattle sustainability can be maintained.